A first look at whale sharks in Hawaiian waters: Using citizen science to study the world's largest fish, Rhincodon typus. Issue 3 (20th January 2023) - Marcoux, Travis M.; Marcoux, Stacia D.; Harvey, Maria; Araujo, Gonzalo
Abstract: The world's largest fish, the whale shark ( Rhincodon typus ), is a circum‐tropically distributed and globally endangered species, that is widely studied at predictable aggregation sites. The main Hawaiian Islands are not known to have large aggregations of whale sharks; however, they have been anecdotally reported here with some regularity. To date, little is known about this charismatic species in Hawaiian waters. This study is the first effort to examine whale shark demographics and movements in a previously unstudied region of the world. Here, citizen science was used to investigate the abundance, seasonality (if any) and occurrence of whale sharks in the waters around the main Hawaiian Islands. A total of 309 individual whale sharks were identified from sightings between 1991–2020 by their unique spot patterns, most of which (74%) were reported between 2018 and 2020. Estimated whale shark total length ranged from 2–12 m (mean 6.1 m), with both juvenile and mature males and females represented in the dataset. The best‐fit Lagged Identification Rate (LIR) model for these data suggests that individuals sighted in Hawaiian waters are transient in nature, supporting the empirical data (88% of sharks sighted only once). Although using citizen science data can have inherent biases, these results present a conservative first assessment of the demographics of whale sharks in Hawaiian waters. For an Endangered species assessed as Largely Depleted by the IUCN Green Status of Species, highlighting Hawai'i as an important habitat for the whale shark – mainly as a migratory corridor or navigational waypoint – is a crucial step in understanding their ecology in the Pacific in order to develop effective management plans.